Prospects of breeding small ruminants for resistance to internal parasites - Woolaston, R.R.; Baker, R.L. (Elsevier, 1996)
Resistance to nematode parasites can be improved by selection, but efforts to include appropriate traits in commercial livestock breeding programs are only a recent development. Procedures for including resistance in breeding programs are similar to those involving other traits. The steps are described with special reference to sheep, and areas are highlighted where particular considerations exist. Three approaches are described and contrasted: breeding for resistance (reduced parasite numbers, as determined by faecal worm egg count); resilience (production during parasitism); or number of treatments required during parasitism. It is necessary, but difficult, to assess the economic benefits of improving resistance relative to other traits. Disease costs vary widely depending on the prevalence of the disease and on the availability, effectiveness and sustainability of alternative control measures. Costs of treatment and control are relatively simple to estimate for a given situation, but production losses are more difficult. Methods of dealing with this problem are discussed. Breeding for disease resistance usually requires that either selection candidates, or their relatives, are exposed to the pathogen so that resistance levels can be compared. Parasitic diseases generally create no special ethical problems in a breeding program unless natural challenge levels are insufficient to enable discrimination between hosts in their susceptibility. In the longer term, it is desirable that selection criteria for all major diseases be developed that will be informative in healthy animals. Molecular genetic markers offer promise, but simple genetic markers have so far been as elusive as physiological traits to predict resistance in undiseased animals. In the longer term, useful genetic markers will be found and techniques for combining these with phenotypic information need to be developed. Commercial breeding programes for sheep which include resistance to gastrointestinal roundworms are now operating in Australia and New Zealand, and issues related to breeding in the tropics are discussed.